Business model - an ephemeral trend or a claim of the future? the orientation of enterprises within the agricultural machinery sector = Model biznesu - efemeryczny trend czy postulat przyszłości? orientacja przedsiębiorstw sektora maszyn rolniczych - Nogalski, Bogdan; Niewiadomski, Przemysław (Zielona Góra: Faculty of Economics and Management Press)
The fundamental objective of this research paper is to determine whether contemporary management is recognized traditionally, in the light of a strategy and the entailing methods of operation, adapted to the target recipients, based on knowledge and studies, strongly embedded in the market reality or perhaps more as a paradigm, in which the focal point is the architecture of business processes, which comprises a description of their conceptualization, the determination of individual and necessary stages of operations and the modelling of these process, i.e., a business model.
Keywords: Zarządzanie strategiczne; model biznesowy; strategia; producent maszyn rolniczych; strategic management; business model; strategy; agricultural machinery manufacturer